RHOMOLO: A Dynamic General Equilibrium Modelling Approach to the Evaluation of the EU's Regional Policies - Ben Gardiner; D'Artis Kancs (European Regional Science Association (ERSA), 2011)
This paper describes some of the features of a new dynamic general equilibrium framework (RHOMOLO) being developed at the European Commission (JRC-IPTS, together with DG REGIO) for evaluating EU Cohesion Policy. The design of the model reflects the objectives of Cohesion Policy, and a broader understanding of impact analysis which goes beyond pure economic effects and also considers environmental and social indicators. The model has both regional and sectoral dimensions - regionally, the aim is for complete NUTS2 (NUTS1 for Germany) coverage of the EU27, while the potential sector coverage is 23 - all of which leads to very large modelling dimensions and presents challenges in terms of data availability. The model is constructed using the concept of Dynamic Spatial Computable General Equilibrium (DSCGE), which ensures Walrasian equilibrium in a sequence of model solutions over time, and also incorporates elements of New Economic Geography (NEG) in the way it captures the forces of economic agglomeration and dispersion.
Keywords: 330